SINDIRAN MELALUI PELANGGARAN MAKSIM KUANTITAS DI ACARA TV LAPOR PAK! - Fibiani, Mufadila; Devina, Nadia Irma Della; Astutiningtyas, Dessy; Nurhayani, Ika (Jurnal Budaya, 2021)
This study focuses on the form of satire through the violation of the maxim of quantity in the TV show Lapor Pak! and the government's response to the satire that was conveyed. This type of research is qualitative. The data is taken from the utterances of the cast of the TV show Lapor Pak!. The data source is the tiktok account @laporpak_trans7. The data was collected using the free-of-conversation listening technique which was then analyzed through the interactive model of Miles and Huberman. The results showed that the satire was conveyed through the violation of the maxim of quantity. As for the practice, despite having to violate the maxim of quantity, the goal in communication has been achieved, namely in the form of satire. The types of satire expressed in the form of irony, parody, and satire itself.